Ieee Infocom 2009 2009
DOI: 10.1109/infcom.2009.5062010
|View full text |Cite
|
Sign up to set email alerts
|

Network Pricing and Rate Allocation with Content Provider Participation

Abstract: Abstract-Pricing content-providers for connectivity to endusers and setting connection parameters based on the price is an evolving model on the Internet. The implications are heavily debated in telecom policy circles, and some advocates of "Network Neutrality" have opposed price based differentiation in connectivity. However, pricing content providers can possibly subsidize the end-user's cost of connectivity, and the consequent increase in end-user demand can benefit ISPs and content providers. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 15 publications
0
67
0
Order By: Relevance
“…additional transit revenue from the content provider in a two sided" payment model to ISP1 [4,7]. Then, unless D = 0 there is no optimal p 3 : as it increases, so does U 1 .…”
Section: Discussion Of Side Paymentsmentioning
confidence: 99%
“…additional transit revenue from the content provider in a two sided" payment model to ISP1 [4,7]. Then, unless D = 0 there is no optimal p 3 : as it increases, so does U 1 .…”
Section: Discussion Of Side Paymentsmentioning
confidence: 99%
“…Network Neutrality in Network Utility Maximization Issues Hande et al [39] consider the two-sided market in a quite different context. Instead of using the predefined price-demand curve, they look into the network utility maximization with the participation of the CPs.…”
Section: Regulation Mechanisms Based On Cooperative Gamesmentioning
confidence: 99%
“…We use a function g(·) defined on [0, 1] to express the QoS provided by NSP S2 as q2 = g(λ2). For simplicity, we assume as in [4] that the cost of serving subscribers is fixed and smaller than the level that drives the NSPs out of the market so that we can use revenue maximization as the objective of the NSPs.…”
Section: System Modelmentioning
confidence: 99%
“…For instance, without considering the interplay between different NSPs, the authors in [4] formulated a rate allocation problem by incorporating the participation of content providers into the model, and derived equilibrium prices and data rates. In [5], the authors showed that non-cooperative communications markets suffer from unfair revenue distribution among NSPs and proposed a revenue-sharing mechanism that requires cooperation among NSPs.…”
Section: Related Workmentioning
confidence: 99%